ANALISIS MODEL PEMBELAJARAN RADEC (Read, Answer, Discuss, Explain, Create) DALAM MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA SEKOLAH DASAR : LITERATURE REVIEW - Ghania, Nabila Zahra; Gunawan, Dani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading comprehension is a basic competency that elementary school students must possess. However, in practice, many students still experience difficulties in understanding reading content. This study aims to analyze the effectiveness of the RADEC (Read, Answer, Discuss, Explain, Create) learning model in improving elementary school students' reading comprehension. The method used was a literature review. Journal searches were conducted on Google Scholar and relevant articles. The analysis results indicate that the RADEC model can improve reading comprehension because it encourages students to actively read, think critically, discuss, and construct understanding independently. Thus, the RADEC model can be an effective learning alternative in improving elementary school students' literacy skills.